Cytotoxic activity and apoptosis induction of avocado Persea americana Mill. seed extract on MCF-7 cancer cell line - Yuli Widiyastuti; Rarastoeti Pratiwi; Sugeng Riyanto; Subagus Wahyuono (Indonesian Journal of Biotechnology, 2018)
Avocado Persea Americana Mill. is a commercially important crop and studies have shown that the pulp may have benefits to cardiovascular health, dermatological health and possibly anti-cancer activity. Avocado seeds have several medicinal properties such as anti-hyperglycemic, antimicrobial, antioxidant and anti-inflammation. This study aim to evaluate the effect of avocado seed extract on viability and apoptosis of breast cancer cell line MCF-7. The anticancer effect was evaluated by cytotoxic test using MTT assay and the effect on apoptosis and cell cycle was examined by flow cytometry method. The cytotoxic test showed that chloroform extract had strong cytotoxic activity against MCF-7 cell lines with IC50 value of 94.87 µg/mL. Furthermore, the chloroform extract was partitioned with methanol and yield of soluble methanol fraction (FLM) and non soluble methanol fraction (FTLM). The cytotoxic activity of the methanol soluble fraction (FLM) and non soluble methanol fraction (FTLM) against MCF-7 cell lines was increased with IC50 of 34.52 and 66.03 µg/mL, respectively. Flow cytometry analysis using annexin-V and propidium iodide staining revealed that methanol soluble fraction could induce apoptosis and modulating the cell cycle arrest in MCF-7 cell. This research indicated that avocado seed has a potency to induce apoptosis and as anti-proliferative to MCF-7 cells lines.